LOVE YOURSELF, LOVE OTHERS: MENGAJARKAN SISWA SD MENGHARGAI DIRI SENDIRI DAN SESAMA - Claudes, Juniven; , Nivia; Utomo, Mochamad Hammam Tegar; Oktariana, Putri; Saputro, Bayu Eko; Setiawan, Dany; Dewi, Fransisca Iriani R. (Jurnal Serina Abdimas, 2024)
School is a place where children learn and develop themselves. Children studying in primary school are developing their character and social skills through interaction with the wider social environment. Therefore, the school social environment is quite crucial. Bullying and self-harm among elementary school students are serious problems that can have a negative impact on children's mental and emotional development. At SDN P, bullying behavior was found among students in grades 4 to 6, as well as several cases of self-harm among students in grades 5 and 6. This has a negative impact on the well-being of students at school. Therefore, a psychoeducational activity entitled "Love Yourself, Love Others" was held to increase students' understanding of the negative impact of bullying and the importance of self-love, so as to reduce bullying and self-harm behaviors. The methods used in this activity include psychoeducation that provides material on bullying and self-love, experience sharing sessions, and self-report activities. The implementation of activities involves direct interaction with students, data collection through observation and self-report. The results of the activity showed an increase in students' awareness of the importance of stopping bullying and practicing self-love. Thus, the "Love Yourself, Love Others" activity successfully made a positive contribution in creating a healthier school environment and supporting students' mental development and well-being. This program demonstrates that education on mental health and positive values can be effectively implemented at the primary school level to address the issues of bullying and self-harm. ABSTRAK Sekolah merupakan tempat anak belajar dan mengembangkan diri. Anak yang menempuh pendidikan SD sedang mengembangkan karakter serta kemampuan sosial melalui interaksi dengan lingkungan sosial yang lebih luas. Oleh sebab itu, lingkungan sosial sekolah merupakan hal yang cukup krusial. Bullying dan self-harm di kalangan siswa sekolah dasar menjadi masalah serius yang dapat berdampak negatif pada perkembangan mental dan emosional anak. Di SDN P, ditemukan adanya perilaku bullying di antara siswa kelas 4 hingga 6, serta beberapa kasus self-harm di kalangan siswi kelas 5 dan 6. Hal tersebut berdampak negatif pada kesejahteraan siswa-siswi di sekolah. Oleh sebab itu, kegiatan psikoedukasi yang berjudul "Love Yourself, Love Others" diadakan untuk meningkatkan pemahaman siswa-siswi tentang dampak negatif bullying dan pentingnya self-love, sehingga dapat mengurangi perilaku bullying maupun self-harm. Metode yang digunakan dalam kegiatan ini meliputi psikoedukasi yang memberikan materi tentang bullying dan self-love, sesi berbagi pengalaman, dan kegiatan self-report. Pelaksanaan kegiatan melibatkan interaksi langsung dengan siswa, pengumpulan data melalui observasi dan self-report. Hasil kegiatan menunjukkan adanya peningkatan kesadaran siswa terhadap pentingnya menghentikan bullying dan mempraktikkan self-love. Dengan demikian, kegiatan "Love Yourself, Love Others" berhasil memberikan kontribusi positif dalam menciptakan lingkungan sekolah yang lebih sehat serta mendukung perkembangan mental dan kesejahteraan siswa. Program ini menunjukkan bahwa edukasi tentang kesehatan mental dan nilai-nilai positif dapat secara efektif diterapkan di tingkat sekolah dasar untuk mengatasi masalah bullying dan self-harm